Oil Palm Tourism as a Strategy for Sustainability and Positive Engagement: A Preliminary Case Study for SD Guthrie EcoGardens - Ruslan, Noraini; Mohamad Zakariah, Muhammad Haqim; Abdul Kadir, Muhammad Azraie; Othman, Muhammad Fakri; Abdul Rapar, Ezzaruddin (Journal of Sustainable Natural Resources, 2025)
The oil palm industry, crucial to tropical nations like Malaysia, frequently faces environmental criticisms that impact its global reputation. Negative perceptions often stem from misinformation and limited firsthand exposure, leading to misconceptions about its sustainability efforts. This exploratory pilot study examines the potential of oil palm tourism as a strategy to address these concerns by fostering direct engagement and education. A preliminary case study was conducted at SD Guthrie EcoGardens (SDGE) in June 2023, involving on-site surveys with 15 visitors (aged 21–23) to assess perceptions of oil palm’s environmental sustainability, socio-economic impact, community involvement, cultural preservation, educational value, and infrastructure sustainability. Using a 5-point Likert scale (1 = Very Poor to 5 = Excellent), the overall evaluation score was 4.3, with infrastructure sustainability (4.5) rated highest, followed by environmental sustainability and cultural preservation (4.4), educational impact (4.3), socio-economic contributions (4.2), and community involvement (4.0) as the lowest-rated aspect. Findings highlight oil palm tourism’s potential as a strategic investment to enhance public perception, stimulate economic benefits, and improve industry transparency. However, as this is a preliminary case study with a limited sample size, further large-scale research is necessary to validate these findings and examine the long-term impact of oil palm tourism. Wider adoption of oil palm tourism, supported by increased funding for community engagement, cultural integration, and infrastructure development, could strengthen global support for the industry and establish oil palm tourism as a high-value eco-tourism and sustainability initiative.